How close to home does charity begin?. Issue 34 (20th July 2020) - Grimson, Duncan; Knowles, Stephen; Stahlmann-Brown, Philip
ABSTRACT: This paper uses a field experiment to analyse the extent to which people are more inclined to support a charity focused on people or causes in their own region, compared to regions in other parts of the country. New Zealand landowners were incentivized to take part in an online survey by being told they could choose a charity from a list of four that would receive a $10 donation if they completed the survey. Importantly, the charities are based in different regions of the country. We find evidence of a significant declining radius of altruism: not only do people prefer to support charities in their own area, the further away a charity is located, the less likely people are to support it. These findings highlight the importance of geographic distance (independent of social distance) in charitable giving.